1986
DOI: 10.1111/j.1365-2362.1986.tb01308.x
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II, aldosterone and arginine vasopressin in plasma in congestive heart failure

Abstract: Angiotensin II (AII), aldosterone (Aldo) and arginine vasopressin (AVP) in plasma were determined during basal conditions in seventeen patients with congestive heart failure and in seventeen control subjects. The same parameters were measured before and 1, 2 and 3 h after an oral water load of 20 ml (kg body weight)-1 together with urine volume (V) and free water clearance (CH2O) in seven patients with congestive heart failure and in seven control subjects. AII, Aldo and AVP were significantly higher in heart … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
24
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 26 publications
5
24
0
Order By: Relevance
“…27 Previous human studies performed under similar experimental conditions have shown that plasma Ang II may increase from 15 to 57 pmol/L after a 2-hour infusion of 1.5 ng/kg per minute 29 or from 20 to 25 to 50 to 70 pmol/L with stepwise increasing doses of Ang II from 0.3 to 3.0 ng/kg per minute each for 30 minutes. 28 Such levels of plasma Ang II were roughly the same observed in human pathophysiological conditions such as CHF 31 and renovascular hypertension. 32 Thus, although we could not measure plasma Ang II, our infusion protocol was designed in the assumption that a stepwise increasing rate of 0.625 to 2.5 ng/kg per minute Ang II would have produced a progressive elevation in plasma Ang II from low baseline levels toward physiological and, later, pathophysiological concentrations.…”
Section: Discussionmentioning
confidence: 63%
“…27 Previous human studies performed under similar experimental conditions have shown that plasma Ang II may increase from 15 to 57 pmol/L after a 2-hour infusion of 1.5 ng/kg per minute 29 or from 20 to 25 to 50 to 70 pmol/L with stepwise increasing doses of Ang II from 0.3 to 3.0 ng/kg per minute each for 30 minutes. 28 Such levels of plasma Ang II were roughly the same observed in human pathophysiological conditions such as CHF 31 and renovascular hypertension. 32 Thus, although we could not measure plasma Ang II, our infusion protocol was designed in the assumption that a stepwise increasing rate of 0.625 to 2.5 ng/kg per minute Ang II would have produced a progressive elevation in plasma Ang II from low baseline levels toward physiological and, later, pathophysiological concentrations.…”
Section: Discussionmentioning
confidence: 63%
“…Thus, the sensitivity to AI within the splanchnic vascular bed, as indicated by SVR increase, was diminished to a value of 0.2 ± 0.1 after cilazapril, indicating that at AII plasma concentrations comparable with those in congestive heart failure (Staroukine et al, 1984;Pedersen et al, 1986) the splanchnic vasoconstriction was strongly suppressed. It therefore appears that the ACE inhibition may be beneficial in avoiding splanchnic (mesenterial) vasoconstriction and that this may be of clinical importance in haemodynamic conditions accompanying congestive heart failure (Staroukine et al, 1984;Menge, 1986;Bailey et al, 1987).…”
Section: Discussionmentioning
confidence: 94%
“…Thus, RAS-dependent vasoconstriction reaches greatest importance in patients with congestive heart failure and other low cardiac output states (McNeill et al, 1970(McNeill et al, , 1982Staroukine et al, 1984;Bailey et al, 1987). It was demonstrated that in most patients with myocardial pump failure not only were increased catecholamine plasma levels found (Vignerat et al, 1985), but also plasma renin activity and AII plasma concentrations were elevated (Pedersen et al, 1986), AII being positively correlated with PCWP and negatively correlated with CO, thus, reflecting the severity of myocardial failure (Staroukine et al, 1984).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neurohumoral factors including RAAS factors increase fluid retention [17]. Angiotensin-II, in particular, increases vasopressin, which weakens the effect of TLV somewhat, and aldosterone, which is the final product of the RAAS, increases retention of sodium and water in the renal tubules and is thus thought to act against the effects of TLV [18][19][20]. Neither carperitide nor any inotropic agent that would enhance RAAS activity in patients with ADHF was used in this study.…”
Section: Raas Activity and The Clinical Effect Of Tlv During Early Phmentioning
confidence: 99%